Exposure to nitrites from meat products as food additives among adolescents in Poland - Katarzyna Stoś; Barbara Wojda; Maciej Ołtarzewski; Joanna Gajda-Wyrębek; Marta Dmitruk; Jacek Postupolski (Roczniki Panstwowego Zakladu Higieny)
Background Nitrites should be limited in the diet because their potential carcinogenic effects. However, the addition of nitrites is essential to maintain the microbiological safety of meat products, mainly to protect them from bacteria Clostridium botulinum and to preserve the pink colour of meat products and to give them desirable organoleptic properties. Acceptable Daily Intake (ADI) for nitrite (expressed as nitrite ion) established by EFSA is 0.07 mg per kilogram of body weight per day (mg kg −1 day −1 ), equivalent to 0.1 mg kg −1 day −1 of sodium nitrite.